Current measurement methods for the smart grid - Kirkham, H. (2009 IEEE Power & Energy Society General Meeting, 2009)
Fundamentally, the measurement of current in a power system means the obtaining of a representation of that current at a distant location. The application determines the requirements on the measurement. Will an rms value suitable for a once-per-second SCADA scan be adequate, or does the ldquorepresentationrdquo have to be an accurate copy up to (say) 100 kHz. If so, how accurate does the measurement have to be? The smart grid of the future will doubtless bring additional requirements to the subject of current measurement. For example, since the IEEE standard on interconnecting distributed resources (IEEE Std 1547) requires that no more than 0.5% of the rated current be injected as dc, it seems likely that at least some current measurement systems will require a frequency response extending down to dc. This paper examines the requirements on the measurement imposed by some of the future smart grid functions, and discusses possible solutions.